2023
DOI: 10.1021/acs.jpcc.3c00183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Molecular Structure of Surface Vanadia on Activity and Regenerability of VOx/In2O3 Catalysts for CO2-Assisted Oxidative Dehydrogenation of Propane

Abstract: Our recent work has reported that higher propylene selectivity and improved stability can be achieved by combining redoxactive VO x and basic In 2 O 3 for CO 2 -assisted oxidative dehydrogenation of propane (CO 2 -ODHP). In the present work, we continued to explore the stability and regenerability of V/In catalysts. In particular, our interest lies in identifying the effect of mono-and polyvanadate on catalytic performance and regenerability. A V/In catalyst with an increased proportion of monovanadate was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In conclusion, the configurations of VO x /Ti 3 AlC 2 catalysts are reasonably proposed based on previous reports 19,31,37,53 and the analysis of XRD, SEM, TEM, Raman, H 2 -TPR and XPS results. As shown in Fig.…”
Section: Resultssupporting
confidence: 68%
“…In conclusion, the configurations of VO x /Ti 3 AlC 2 catalysts are reasonably proposed based on previous reports 19,31,37,53 and the analysis of XRD, SEM, TEM, Raman, H 2 -TPR and XPS results. As shown in Fig.…”
Section: Resultssupporting
confidence: 68%
“…This feature has been the focus of several literature reports due to its distinct behavior under the reaction conditions, and it is believed that it is associated with the stretching modes of Mo−O−X configurations, where X can be either another molybdenum atom (bridging bond in oligomers) and/or the cation of the support (anchoring bond). 7,23,32,41,48,49,52,53,55,63,73,74,83,86,87 Structural implications of this band are discussed in more detail in later sections.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Among the strategies to understand the issue of heterogeneity in dispersed oxide sites, in situ vibrational spectroscopy , has proved to be a powerful tool, able to provide molecular-level information on the structural response of deposited oxometallic phases. Particularly, both Raman and infrared (IR) spectroscopies have revealed that the arrangement of dispersed oxo-molybdenum species can vary greatly, especially when deposited on different metal oxide supports.…”
Section: Introductionmentioning
confidence: 99%